Facilitating Molecular Activation and Proton Feeding by Dual Active Sites on Polymeric Carbon Nitride for Efficient CO2 Photoreduction. (17th October 2022) - An, Xiaoqiang; Tang, Qingwen; Lan, Huachun; Liu, Huijuan; Yu, Xuelian; Qu, Jiuhui; Lin, Huiwen; Ye, Jinhua
Abstract: Photoreduction of CO2 provides an appealing way to alleviate the energy crisis and manage the global carbon balance but is limited by the high activation energy and the rate‐limiting proton transfer. We now develop a dual‐site strategy for high‐efficiency CO2 conversion through polarizing CO2 molecules at pyridine N vacancies and accelerating the intermediate protonation by protonated pyridine N adjacent to nitrogen vacancies on polymeric carbon nitride. Our photocatalysts with atomic‐level engineered active sites manifest a high CO production rate of 1835 μmol g −1 h −1, 183 times higher than the pristine bulk carbon nitride. Theoretical prediction and experimental studies confirm that such excellent performance is attributed to the synergistic effect between vacant and protonated pyridine N in decreasing the formation energy of the key *COOH intermediates and the efficient electron transfer relay facilitated by the defect‐induced shallow trap state and homogeneous charge mediators. Abstract : Dual‐site synergism of vacant and protonated pyridine N in polymeric C3 N4 significantly polarized the inert CO2 molecules and eliminates the formation energy barrier of key *COOH intermediates, inducing a state‐of‐the‐art activity enhancement (183 times) in CO production. Our atomic‐precision strategy offers a promising way to overcome the technical challenges in molecular activation and rate‐limiting proton transfer during CO2 photoreduction.